Collaborative planning, forecasting, and replenishment : how to create a supply chain advantage - Seifert, Dirk (AMACOM, 2003)
"Based on original research conducted at the Harvard Business School, Collaborative Planning, Forecasting, and Replenishment gathers the insights and experiences of 38 leading CPFR practitioners from around the world and from a variety of industries, including manufacturers, retailers, consulting companies, and IT-solutions providers. Packed with valuable case studies and insider accounts from some of the most powerful companies using CPFR today - including giants such as Wal-Mart, Safeway, Ace Hardware, and Procter & Gamble."